Are Backbenchers Fighting Back? Intra-Party Contestation in German Parliament Debates on the Greek Crisis. Issue 2 (22nd February 2018) - Bhattacharya, Caroline; Papageorgiou, Achillefs
Abstract: Over the course of the Eurozone crisis, we have witnessed a disintegration of the pro-European consensus in the German Bundestag. This study focuses on patterns of intra-party contestation by examining individual-level determinants of the growing party disunity. Party leaders constrain the room of manoeuvre of individual legislators, but the degree of party control they face varies depending on their position within the party, and we expect this to be reflected in their behaviour. Our comprehensive case study of plenary debates on the Greek crisis in the Bundestag (2010–2015) analyses legislative speech, voting defection and explanations of vote. Our results show that an MP's rank, experience, electoral mandate and gender matter in their inclination to voice dissent. Here, the frontbencher–backbencher categorisation shows the most consistent effect.